1990
DOI: 10.3109/01421599009006698
|View full text |Cite
|
Sign up to set email alerts
|

The employment of ward opinion leaders for continuing education in the hospital

Abstract: Opinion leaders (OLs) are members within a social group with significant social influence over others. A guideline on urinary catheter care was introduced in three groups (A, B and C) of two randomly allocated wards. Two OLs per ward were identified by nurses in groups A and B, using a sociometric method. For education, inservice lectures for 30% of nurses and OLs tutorials for all nurses were used in group A; OLs tutorials in B, lectures in C and ward nurses were in turn responsible for educating new arrivals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 6 publications
0
50
0
Order By: Relevance
“…He is a member who has significant social influence over others within a social group. 64 The key to success of the opinion leader strategy is the improvement of feedback and acceptance of the local intervention, 24,27 but his action is not systematically efficient alone. Sisk et al 27 showed that, although opinion leaders identified obstacles, they have not found a successful way to influence a mother's behavior.…”
Section: Resultsmentioning
confidence: 99%
“…He is a member who has significant social influence over others within a social group. 64 The key to success of the opinion leader strategy is the improvement of feedback and acceptance of the local intervention, 24,27 but his action is not systematically efficient alone. Sisk et al 27 showed that, although opinion leaders identified obstacles, they have not found a successful way to influence a mother's behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Two had unit of analysis errors where the investigators allocated by group but did not account for clustering in the analysis [24,25]. Of the two studies without unit of analysis errors, the investigators of one study allocated by unit and accounted for clustering [26], while the other allocated and analyzed at the provider level [27].…”
Section: Resultsmentioning
confidence: 99%
“…Both reported non-significant changes in outcomes, which suggests that educational meetings are ineffective. In the third study assessing an educational intervention, the authors examined an interactive educational meeting in addition to a local opinion leader;17 nurses who attended both an educational session and a tutorial led by a local opinion leader reported increased research use. The authors of the fourth study16 investigated the formation of multidisciplinary committees of clinicians and researchers working to operationalise a process to increase research use by oncology nurses; research use by clinicians increased after participation 16…”
Section: Systematic Review: Methods and Findingsmentioning
confidence: 99%
“…Marketers have long recognised the benefits of opinion leaders by way of influential and interpersonal communication 47 48. The review of interventions to increase research use by nurses 14 identified 1 study that reported positive effects of using local opinion leaders 17. In a broader healthcare context, the effect of local opinion leaders as change agents is mixed 10 43 46.…”
Section: Recognising and Crossing Boundariesmentioning
confidence: 99%